Queering Contemporary Asian American Art - Bernabe, Jan Christian; Bernabe, Jan Christian; Kina, Laura 1973-; Kina, Laura 1973- (Book collections on Project MUSE., 2017)
Takes Asian American differences as its point of departure and brings together artists and scholars to challenge normative assumptions, essentialisms, and methodologies within Asian american art and visual culture. Taken together, these nine original artist interviews, cutting-edge visual artworks, and seven critical essays explore contemporary currents and experiences within Asian american art, including the multiple axes of race and identify, queer bodies and forms, kinship and affect, and digital identities and performances. -- back cover.